THE ROLE OF MARKETING SERVICEIN THE ACTIVITY OF THE ENTERPRISE - KOVALCHUK, S.; RYASNYKH, A.; BOLOTNIKOVA, H. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Marketing service - a special unit that operates on the basis of principles and methods of marketing. This unit acts as a buffer between the external environment - the market and the internal environment - the company. In order for the marketing department to successfully implement its tasks, it is necessary to determine its place.Marketing services can have two levels of management: central marketing departments; operational departments or sectors. The marketing department is not just a production and sales service unit, but a coordinating, planning and controlling body of strategic production and sales management. In the practice of foreign firms, the structure of marketing structures is diverse. The most widespread are linear-functional management structures by types (functions) of marketing activities, by products and regions.The functions of the marketing department are closely related to the functions of other divisions of the production department: departments of internal planning, financing and pricing, as well as the central marketing service, which coordinates all production departments of the firm. The central marketing service is the main body through which this management function is implemented. The central marketing department develops the company's goal and strategy based on marketing programs for each product received from production departments. This service is closely linked with the central services of planning, finance, control, which provides a comprehensive approach to addressing issues related to the organization of production and marketing activities of the firm. Decisions on the most important issues of marketing activities are made by the highest level of management - the board of directors or the board with the participation of leading experts in the field of entrepreneurship.